2022
DOI: 10.3389/fpsyt.2022.824234
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Food Addiction and Weight Status in School-Age Children and Adolescents

Abstract: BackgroundThe association between food addiction (FA) and weight status in children and adolescents remains poorly understood. This study aimed to elucidate the association between FA and weight status using the validated Chinese version of the dimensional Yale Food Addiction Scale for Children 2.0 (dYFAS-C 2.0).MethodsParticipants were enrolled from clinic visitors for regular physical check in a children’s hospital. The dYFAS-C 2.0 was translated into Chinese and validated using reliability and validity test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Interestingly, this study found that female (but not male) BMI z-scores and socio-economic status (SEIFA) were significantly correlated with the total FA (YFAS-C) symptom score (r = 0.115, p < 0.001, and r = −0.066, p = 0.005, respectively); however, they were not found to be significant in the regression model. Several studies have recently reported significant positive correlations between FA symptoms and BMI z-scores [ 54 , 55 , 56 ], indicating that as BMI z-score increases YFAS symptom score also increases. While income appears to be associated with unhealthy eating behaviours and obesity [ 57 ], the link between socio-economic status and FA is currently limited with one study reporting similar findings of greater YFAS symptoms related to increased BMI and low household income [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this study found that female (but not male) BMI z-scores and socio-economic status (SEIFA) were significantly correlated with the total FA (YFAS-C) symptom score (r = 0.115, p < 0.001, and r = −0.066, p = 0.005, respectively); however, they were not found to be significant in the regression model. Several studies have recently reported significant positive correlations between FA symptoms and BMI z-scores [ 54 , 55 , 56 ], indicating that as BMI z-score increases YFAS symptom score also increases. While income appears to be associated with unhealthy eating behaviours and obesity [ 57 ], the link between socio-economic status and FA is currently limited with one study reporting similar findings of greater YFAS symptoms related to increased BMI and low household income [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…BMIZ, body mass index z-score; FC, fat content; VFL, visceral fat level. score of 0.7 was strongly associated with higher BMIZ and could be an indicator of high FA risk (23). In this study, participants with a high risk of FA at baseline had a 2-3 times probability of being diagnosed as excessive weight during follow-up.…”
Section: Discussionmentioning
confidence: 57%
“…The participants' additive-like eating behavior was characterized using the FA scores assessed by the Chinese version of the dimensional Yale Food Addiction Scale for Children 2.0 (dYFAS-C 2.0) (23). In 2018, Schiestl and Gearhardt (24) developed the dYFAS-C 2.0 based on the Diagnostic and Statistical Manual for Mental Disorders, fifth edition.…”
Section: Food Addictionmentioning
confidence: 99%
See 2 more Smart Citations